Sukuk rating and earnings response coefficient / Nor Balkish Zakaria, Mohamad Azwan Md Isa , Rabiatul Alawiyah Zainal Abidin - Zakaria, Nor Balkish; Md Isa, Mohamad Azwan; Zainal Abidin, Rabiatul Alawiyah (2013)
Abstract Purpose - This paper empirically examines the effect of Sukuk (Islamic bond) rating as an additional risk in explaining the earning response coefficient Design/methodology - A sample of to 2011 were examined by using reverse regression method. Findings - The study finds that Sukuk rating is strongly correlated to default risk measure and Sukuk rating is significant and negative to ERC. Originality/value - The study thus provides systematic and comprehensive evidence on the effect of Sukuk rating on ERC. Keywords: Sukuk rating, defaul risk